DNA methylation subpatterns at distinct regulatory regions in human early embryos. Issue 10 (31st October 2018) - Luo, Rongsong; Bai, Chunling; Yang, Lei; Zheng, Zhong; Su, Guanghua; Gao, Guangqi; Wei, Zhuying; Zuo, Yongchun; Li, Guangpeng
Abstract : Abstract : DNA methylation has been investigated for many years, but recent technologies have allowed for single-cell- and single-base-resolution DNA methylation datasets and more accurate assessment of DNA methylation dynamics at the key genomic regions that regulate gene expression in human early embryonic development. In this study, the region from upstream 20 kb to downstream 20 kb of RefSeq gene was selected and divided into 12 distinct regions (up20, up10, up5, up2, 5'UTR, exon, intron, 3'UTR, down2, down5, down10 and down20). The candidate promoter region (TSS ± 2 kb) was further divided into 20 consecutive subregions, which were termed 'bins'. The DNA methylation dynamics of these regions were systematically analysed along with their effects on gene expression in human early embryos. The dynamic DNA methylation subpatterns at the distinct genomic regions with a focus on promoter regions were mapped. For the 12 distinct genomic regions, up2 and 5'UTR had the lowest DNA methylation levels, and their methylation dynamics were different with other regions. The region 3'UTR had the highest DNA methylation levels, and the correlation analysis with gene expression proved that it was a feature of transcribed genes. For the 20 bins in promoter region, the CpG densities showed a normal distribution pattern, and the trend of the methylated CpG counts was inverse with the DNA methylation levels, especially for the bin 1 (downstream 200 bp of the TSS). Through the correlation analysis between DNA methylation and gene expression, the current study finally revealed that the region bin −4 to 6 (800 bp upstream to 1200 bp downstream of the TSS) was the best candidate for the promoter region in human early embryos, and bin 1 was the putative key regulator of gene activity. This study provided a global and high-resolution view of DNA methylation subpatterns at the distinct genomic regions in human early embryos.